2008
DOI: 10.1016/j.fluiddyn.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical properties of the vorticity vector derived using large-eddy simulation

Abstract: In this paper, the geometrical properties of the resolved vorticity vector ¯ derived from large-eddy simulation are investigated using a statistical method. Numerical tests have been performed based on a turbulent Couette channel flow using three different dynamic linear and nonlinear subgrid-scale stress models. The geometrical properties of ¯ have a significant impact on various physical quantities and processes of the flow. To demonstrate, we examined helicity and helical structure, the attitude of ¯ with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Prototypical geometrical patterns have been reproduced and compared with the reported DNS, experimental and a priori LES results. The present research together with some recently reported LES studies [13,14,16,21,28,58] confirms that LES is an effective tool for investigating the geometrical property of a turbulent field at the resolved-scales.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Prototypical geometrical patterns have been reproduced and compared with the reported DNS, experimental and a priori LES results. The present research together with some recently reported LES studies [13,14,16,21,28,58] confirms that LES is an effective tool for investigating the geometrical property of a turbulent field at the resolved-scales.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Since then, this subject has been extensively studied based on a variety of analytical, experimental and numerical methodologies. A detailed review of the subject can found in the recent work of Wang et al [21]. To date, research on the alignment betweenω and e Sβ has been restricted primarily to isotropic isothermal flows [3,4,13,14,54].…”
Section: Attitude Of the Resolved Vorticity Vector With Respect To Thmentioning
confidence: 99%
See 3 more Smart Citations